ANALISA KERJASAMA SISTER CITY KOTA BANDUNG DAN KOTA SUWON PADA SEKTOR PARIWISATA DAN KEBUDAYAAN PERIODE 2016-2019 - Muhamad Marcelino, (2022)
Diplomacy is one of the instruments used by the State to fulfill its interests. Generally, diplomatic efforts are used by the State to establish good relations with other States. However, diplomacy is not exclusive to States. Non-State entities can also use diplomacy, for example local governments. This form of diplomacy used by local governments is also called paradiplomacy. This study will discuss how the paradiplomacy efforts used by the Bandung city government to increase the capability of the tourism industry. In this diplomatic effort, the Bandung government cooperates with the Suwon government in the form of a Sister City cooperation framework. This study finds that the efforts made by the two governments are still not effective in developing the tourism industry.